DOES TRAINING WITH INCENTIVES WORK? IMPACT EVALUATION OF INDONESIA’S PRE-EMPLOYMENT CARD - Kurniawati, Fathimah (Transpublika Publisher, 2025)
The government's pre-employment card scheme aims to enhance the capabilities of Indonesian workers, making them more competitive and efficient. Simultaneously, it serves as a safety net to alleviate the effects of the Covid-19 crisis. This study seeks to evaluate how the pre-employment card program influences the time taken to prepare for employment and improve skills. The focus is on whether this initiative can decrease the waiting period for job seekers and enhance the skills of the participants. The research utilises the Propensity Score Matching technique and data from the Survei Kerja Nasional in February 2021. The findings suggest that the pre-employment program has a notable positive impact on the skills development of those involved, by 0.08199%. While skill enhancement is evident, the scheme has not led to a reduction in the time it takes for individuals to secure employment. The effectiveness of the program could be enhanced through the implementation of additional policies, including the improvement of labour market information systems and the provision of active employment support services by the government.